Courtyard Compact House: Alternative Living Pattern for Urban Context in Tropical Regions - Phattanawasin, Srisak (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This article proposes the idea of the courtyard compact house, an alternative living pattern for urban context in tropical regions. A plan configuration of courtyard compact house integrates between the contemporary notion of compact house and the advantage of courtyard house from the past by applying an open courtyard for creating an individual outdoor space into an efficient planning of compact house. The open courtyard area not rather serves a variety of social activities in family life but also fits into tropical climate owing to a natural ventilation design method. This design strategy might be an alternative for sufficient architecture in limited area. The contents of this article include history and development of the courtyard house, the compact house, and the courtyard compact house configuration in Thailand and other South East Asian countries. Furthermore, at the end of this article demonstrates the roles of this contemporary design vocabulary reflecting the social and environmental dimensions which are important issues for the development of tropical sustainable architecture in urban context.